Socio-Demographic Factors and Intergenesic Interval in Nicaraguan Immigrant Mothers in Costa Rica - E. Bonilla, Roger; Cardoza, David (Población y Salud en Mesoamérica, 2007)
Adequate birth intervals are considered a positive factor in the health of mothers and their children. One of the objectives of this study is to compare the birth interval between Nicaraguan immigrant women and local mothers in Costa Rica. Birth intervals among Nicaraguan women are significantly shorter than the local ones (p < 0.001). Half of the children of the Nicaraguan mothers have birth intervals of a minimum of 335 days (less than one year). Half of the local children have birth intervals of a minimum of 881 days (2.4 years). A second objective in this study is to fit a Cox’s proportional stratified hazard model of the type in order to λs(t,X) = λo(t)exp(βis,’Xi) model the birth interval as a time-to-event variable (pregnancy of the next child). Fitting by nationality of the mother, age, and age on first birth-delivery, the hazard ratios are respectively 1.3 (p < 0.001), 0.93 (p < 0.001), and 1.02 (p > 0.05). Nicaraguan women are 30% more likely to recur in the following pregnancy as compared with local women. The study of population minorities permits the preparation of public policies on international migration issues.